Toward a new comparative public law of central bank legislation: Designing legislative mandates for central bank private securities assets purchases and nominal GDP targeting - Michael, Bryane; Osaulenko, Svitlana (Central Bank of Montenegro, 2021)
What role could unconventional monetary policy – and particularly unconventional policies like private asset purchases under a quantitative easing or lender of last resort scheme – play in influencing economic growth directly? A wide literature in economics explores the pros and cons of using these policies. However, most studies also point to the uncertain and antagonistic legal basis for such purchases. In this paper, we show how the statutory mandate for nominal GDP targeting could best put in place the legal foundations for such asset purchases. We review the legislative and regulatory bases for private securities purchases made by central banks in a sample of countries. We discuss – if legislators and policymakers wanted to – how they might introduce clearer mandates to make such purchases into their public law. We finally show how legal authorizations for GDP targeting might (and probably should) provide for such authorisations. Our discussion sheds light on the fascinating and almost completely ignored area of public law, namely central bank law.

Яку роль може відігравати нетрадиційна монетарна політика – і особливо нетрадиційна політика, як-от купівля приватних активів за схемою кількісного пом’якшення або кредитора останньої надії – у прямому впливі на економічне зростання? Широка література з економіки досліджує плюси та мінуси використання цих політик. Проте більшість досліджень також вказують на невизначеність та антагоністичну правову основу для таких закупівель. У цій статті ми показуємо, як законодавчий мандат щодо орієнтування на номінальний ВВП може найкращим чином створити юридичні основи для таких придбань активів. Ми розглядаємо законодавчу та нормативну базу для купівлі приватних цінних паперів центральними банками у вибірці країн. Ми обговорюємо – якби законодавці та політики цього хотіли, то могли б ввести чіткіші повноваження щодо здійснення таких закупівель у своєму публічному законодавстві. Нарешті ми показуємо, як юридичні дозволи на орієнтування на ВВП можуть (і, ймовірно, повинні) передбачати такі дозволи. Наша дискусія проливає світло на захоплюючу та майже повністю ігноровану область публічного права, а саме на право центрального банку.
Michael B. Toward a new comparative public law of central bank legislation: Designing legislative mandates for central bank private securities assets purchases and nominal GDP targeting / B. Michael, S. Osaulenko // Journal of Central Banking Theory and Practice. - № 10 (1). - Central Bank of Montenegro, 2021. - Р. 5-38.
Keywords: central bank law; central bank private securities purchases; public (monetary) law; GDP targeting; законодавство про центральний банк; купівля приватних цінних паперів центральним банком; державне (грошове) право; таргетування ВВП; Research Subject Categories::LAW/JURISPRUDENCE::Public law